Produção animal e emissões de gases de efeito estufa em pastos de capim-ipyporã e capim-mulato II no bioma Amazônia - Silva, Débora Samara Morais (2018)
The objective of this study was to evaluate the productivity and emissions of greenhouse gases per product unit in a production system using Nellore steers in Ipyporã and Mulato II grass pastures. The design was in randomized complete blocks with two cultivars (Ipyporã and Mulato II) and four replications, in two seasons (dry and water). The experimental period was from May 31, 2016 to June 1, 2017. Forage mass (MF), forage accumulation (AF) and animal performance were measured every 28 days, determined by the mean daily gain (GMD) and weight gain per area (GPA) of beef cattle of the breed Nelore (Bos taurus indicus), not castrated. The evaluation of greenhouse gases (GHG) of the soil was by means of stationary model’s base-top model arranged randomly in the pickets. The emission of enteric methane (CH4) was determined by automated gas measurement equipment (GreenFeed®, C-Lock, South Dakota, USA). The highest MF was recorded for the cultivar Ipyporã (7717 kg ha-1 ). The values of FA were similar among cultivars, however there was a difference between seasons, with a higher accumulation in the water season (20,805 kg ha-1 ). It was observed the incidence of spittlebug in pastures of mulatto grass II in the rainy season. The average daily gain (ADG) presented a mean of 730 g day-1 in grasses of ipyporã grass and mulatto grass II. The highest GHG emissions occurred after nitrogen fertilization. Each kilogram of accumulated forage yielded 0.041 g of N2O, 337 g of CO2 and -0.032 g of CH4 ha-1 . The highest enteric CH4 emissions occurred for mulatto II grass with a mean of 828 g ha-1 day-1 , while the ipyporã grass averaged 508 g ha-1 day-1 . There is a positive relation (r=0.98) between GPA and CH4 emission, however, the higher the production efficiency the lower the CH4 emission. It is concluded that adequate management of pasture and pasture generated similar patterns of individual animal performance for both cultivars. However, mulatto grass pastures have greater productivity, provided there is pest control. In addition, the pasture management used resulted in low GHG emissions per unit of product.